Strategi pondok pesantren terhadap pendidikan karakter anak - Hasyim, Muhammad Masykur (Maliki Interdisciplinary Journal, 2025)
Children's character education is an important effort in preventing the loss of moral values inherited by the ancestors. In this context, boarding schools have a strategic role as educational institutions that not only instill religious knowledge but also build character through an Islamic values approach. Islamic boarding schools are superior because of the dormitory system that allows holistic character building through supervision, intensive interaction, and 24-hour practice of Islamic values. Various strategies are applied to develop the character of santri, such as learning adab, studying classical books, and fostering praiseworthy morals. Nevertheless, challenges such as the influence of modern technology and the lack of full support from parents remain obstacles that need to be overcome. Character education is not only the responsibility of schools, but also the environment, including family and society. Islamic boarding schools, with their unique traditions and systems, have proven their effectiveness in producing a generation with noble character and positive contributions to society